2020
DOI: 10.1111/aas.13700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tranexamic acid on markers of inflammation in children undergoing craniofacial surgery

Abstract: Background Tranexamic acid (TXA) reduces blood loss and transfusion requirements during craniosynostosis surgery in small children. Possible interaction from TXA on the inflammatory system is unknown. Objective To evaluate the effect of TXA on a wide range of inflammatory markers in children receiving TXA in a randomized, blinded, and placebo controlled study design. Methods Thirty children undergoing craniosynostosis surgery with significant blood loss received TXA (bolus dose of 10 mg kg−1 followed by 8 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…19,[47][48][49][50] The majority of included studies were RCTs, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][35][36][37][38][39][40]43,44,[46][47][48][49][50] while five were cohort studies including a control group. 19,34,41,42,45 The participants in most of the articles were undergoing elective surgery (n ¼ 3,563) 19-39,41--47,49,50 of which 13 studies investigated total knee arthroplasty patients which, at least partly, is an inflammatory condition (n ¼ 1,918), 20,22,24,25,27,34,35,[37][38][39]42,...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19,[47][48][49][50] The majority of included studies were RCTs, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][35][36][37][38][39][40]43,44,[46][47][48][49][50] while five were cohort studies including a control group. 19,34,41,42,45 The participants in most of the articles were undergoing elective surgery (n ¼ 3,563) 19-39,41--47,49,50 of which 13 studies investigated total knee arthroplasty patients which, at least partly, is an inflammatory condition (n ¼ 1,918), 20,22,24,25,27,34,35,[37][38][39]42,...…”
Section: Resultsmentioning
confidence: 99%
“…19 The studies were grouped depending on the control group. Fourteen studies compared patients receiving TXA with a group receiving either placebo or no medication 19,20,25,26,29,30,32,34,36,40,42,[48][49][50] while 14 other studies compared different dosing schemes of TXA. [21][22][23][24]28,33,[37][38][39]41,43,44,46,47 Finally, five studies examined the difference of the inflammatory effect of TXA between different administration forms of TXA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the reviewed studies, fifteen assessed the use of TXA in craniofacial surgery procedures [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Of these, nine were retrospective cohort studies [29-31, 34, 35, 38-40, 42], and six were randomized controlled clinical trials [32,33,36,37,41,43]. Study sample ranged from 25 to 187 patients, apart from a single retrospective cohort study of 1638 patients.…”
Section: Craniofacial Surgerymentioning
confidence: 99%
“…Eight studies reported a notable decline in transfusion requirements, owing to decreased intraoperative bleeding, ranging from 19 to 85% [28,[31][32][33][34][37][38][39]. Other notable outcomes included a clearer surgical field [36], shorter length of hospital stay [40], lower drop in postoperative hemoglobin level, higher postoperative estimated red cell volume [30], and decreased surgical drain Fig.…”
Section: Craniofacial Surgerymentioning
confidence: 99%